Immunotherapy in Ovarian Cancer: Thinking Beyond PD-1/PD-L1 - Chardin, Laure; Leary, Alexandra (Frontiers in Oncology, 2021)
Ovarian cancer (OC) is the most lethal gynecologic malignancy, affecting approximately 1 in 70 women with only 45% surviving 5 years after diagnosis. This disease typically presents at an advanced stage, and optimal debulking with platinum-based chemotherapy remains the cornerstone of management. Although most ovarian cancer patients will respond effectively to current management, 70% of them will eventually develop recurrence and novel therapeutic strategies are needed. There is a rationale for immune-oncological treatments (IO) in the managements of patients with OC. Many OC tumors demonstrate tumor infiltrating lymphocytes (TILs) and the degree of TIL infiltration is strongly and reproducibly correlated with survival. Unfortunately, results to date have been disappointing in relapsed OC. Trials have reported very modest single activity with various antibodies targeting PD-1 or PD-L1 resulting in response rate ranging from 4% to 15%. This may be due to the highly immunosuppressive TME of the disease, a low tumor mutational burden and low PD-L1 expression. There is an urgent need to improve our understanding of the immune microenvironment in OC in order to develop effective therapies. This review will discuss immune subpopulations in OC microenvironment, current immunotherapy modalities targeting these immune subsets and data from clinical trials testing IO treatments in OC and its combination with other therapeutic agents.